Taking the lead: post-2012 climate targets for the North: towards adequate and equitable future climate commitments for industrialised countries - Bernd Brouns; Hermann E. Ott (Wuppertal Institut für Klima, Umwelt, Energie, 2005)
Any definition of adequacy consistent with the objective of the Climate Convention will require increased mitigation efforts in industrialized countries far beyond those levels agreed in Kyoto. This paper, therefore, focuses on future reduction targets for industrialised (Annex I) countries. It starts with an assessment of mid- and long-term targets already adopted in industrialised countries against the backdrop of required emission cuts to keep climate change within tolerable limits. Taking into account their heterogeneous national circumstances, the main part of the paper presents a method for differentiating Annex I countries with a view to assigning future mitigation and financial transfer commitments. This differentiation exercise is based on an analytical approach that was developed in the project "South-North Dialogue - Equity in the Greenhouse". Slightly modifying the original approach the level of reduction targets is determined by the two criteria of "responsibility" and "potential" to mitigate. Obligations to provide financial and technological resources to developing countries, on the other hand, are to be assigned according to the "capability" criteria.
urn:nbn:de:101:1-20091019608
Keywords: 330